Integrating Interior Design and Project Management: The Mediator's Role in Enhancing Organizational Creativity and Efficiency - Mohammad Abutabanjh, Fadi Ahmad; Khaled Mahmoud Alghzawi, Abdel Rahman (Data and Metadata, 2025)
Introduction: The combination of interior design and project management is key to improving organizational creativity and efficiency. As firms compete for differentiation, it becomes necessary to optimize the design and management of workspaces. Methods: This research seeks to verify the hypothesis of the relationships between interior design quality, project management effectiveness, and organizational creativity and efficiency with the mediating effect of integration. A close-ended structured questionnaire was administered among 350 managers of Jordanian project management companies quantitatively to collect data. For the analysis the study conducted structural equation modeling (SEM) using Smart PLS 4. Results: The results shed light to confirm the existence of significant positive relationships between IDQ and OCE, PME and OCE, IDQ and INT, and PME and INT. Moreover, integration (INT) serves as a partial mediator between IDQ, PME and OCE. Conclusions: The study suggests that there is a need for a paradigm shift in project management approaches to promote the application of modern interior design techniques for improved organizational innovation and efficiency. Further studies should investigate these findings in other industries and other cultures.